Expression of activin A in liver tissue and the outcome of patients with biliary atresia - Džepina, Petra; Ćorić, Marijana; Kovačić Perica, Matea; Aničić, Mirna Natalija; Grizelj, Ruža; Vuković, Jurica (Frontiers in Pediatrics, 2024)
Biliary atresia (BA) is a rare disease of unknown etiology which leads to cirrhosis and death if left untreated. The standard of care is an early hepatoportoenterostomy (HPE). Long-term follow-up is mandatory, during which most patients will require a liver transplant. Activin A belongs to the transforming growth factor-β (TGF-β) superfamily. TGF-β is a central regulator in chronic liver disease. We have studied the expression of activin A in liver tissue collected intraoperatively during the HPE. We included patients who underwent HPE in a single medical center. Clinical, ultrasonographic, and pathohistological data were collected. Activin A immunostaining was performed. Expression in the bile duct epithelium and hepatocytes was scored as either weakly positive, moderately positive, or strongly positive. Patients were then divided into three groups accordingly. We observed the outcome after the HPE at 3 months, 2 years, and at the end of follow-up. The study encompassed 37 patients. At 3 months after HPE, 92.3% of those with a weakly positive activin A reaction (group A) achieved good jaundice clearance, whereas only 44.4% of those with a moderately (group B) and 40% of those with a strongly positive reaction (group C) achieved good jaundice clearance (p = 0.008). Furthermore, 2 years after the HPE, 92.3% of those in group A survived with native liver (SNL), but only 33.3% of those in group B and 46.7% of those in group C had SNL (p = 0.007). At the end of follow-up, 83.3% of those in group A survived with native liver, as did 33.3% in group B and 40% in group C. Activin A is a valuable pathohistological predictor of the outcome of BA after an HPE.